Phyotochemical screening and anti-microbial screening of potential invasive species found at around Paklihawa, Nepal - Khanal, Subodh; Neupane, Krishna (Himalayan Biodiversity, 2018)
Weed management is one of the great issues in the agroecosystem of this contemporary world. The invasiveness is negatively impacting human and ecosystem as a whole. In this regard, a comparative study was done to investigate the potential phytochemicals and anti-microbial properties present in the problematic invasive species distributed at around Paklihawa Campus, Siddharthanagar, Nepal. Four species viz. Eichornia, Parthenium, Pistia and Ipomoea were selected and the chemical was screened using aqueous methanol as selective menstruum through cold percolation. The fractionated extracts showed the presence of some phytochemicals including alkaloids, saponins, carbohydrates and steroids. Pistia was screening positively for alkaloids, carbohydrates, flavonoids, saponin and steroid; Parthenium for alkaloids, flavonoids and steroids; Eichornia for alkaloids and carbohydrates whereas Ipomoea showed the presence of alkaloids only. The extracts were also screened for antibacterial and antifungal activities. The leaf extracts were used to assess antimicrobial activities against bacteria: Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia and Salmonella typhimurium, and fungi: Aspergillus niger, Candida albicans, Alternaria solani and Fusarium solani using the well diffusion method. The results indicated that the leaf extracts of Parthenium exhibited more zone of inhibition against all bacteria and has potential to be used as anti-bacterial agent. In majority of fungus also, Parthenium was superior to others. The Minimum inhibitory concentration (MIC) values against the tested bacteria ranged from 11 to 19 μg mL-1 and for the tested pathogenic fungi, from 10 to 20 μg mL-1. This result showed that these invasive species could be promising antibacterial and anti-fungal agents.